Cover Feature: Comparison of Oxygen Adsorption and Platinum Dissolution in Acid and Alkaline Solutions Using Electrochemical Quartz Crystal Microbalance (ChemElectroChem 22/2022). Issue 22 (20th October 2022) - Strandberg, Linnéa; Shokhen, Victor; Luneau, Mathilde; Lindbergh, Göran; Lagergren, Carina; Wickman, Björn
Abstract : The Cover Feature illustrates the mass change of a Pt thin film measured during oxygen adsorption/desorption and Pt dissolution during electrochemical cycling in alkaline conditions. More information can be found in the Research Article by L. Strandberg, B. Wickman and co‐workers .